Development of millet based moringa - amla snack bar for iron deficiency in adolescents. - Sandhya, J. Joy; Chinnathambi, Kanniammal (Nutrición Clínica y Dietética Hospitalaria, 2024)
Iron intake is crucial for promoting adolescent health as their growth needs deplete the body’s iron stores. However, junk eating by adolescents leads to inadequate dietary intake. Research studies have shown that incorporating low-cost, non-heme iron-rich moringa leaves into food products, may help meet daily iron needs. Although moringa leaves are a part of everyday diet in South Indian households, underuse is also observed. Aim: To develop a millet-based snack bar, incorporated with dried moringa leaf flour and Amla powder. Methods: Moringa Leaves were procured from local farm. Snack Bar was prepared using Moringa Flour at different concentrations (20%,40% and 60%) and standardized by mixing it with groundnut flour, toasted sesame seeds, Ragi and Kambu millets, dried amla powder ghee, and Jaggery. The sensory evaluation was done using 30 semi trained panel members on a 5 point hedonic rating scale and the accepted product was nutritionally analyzed. Results: The Moringa Amla Millet Bar with a 20% incorporation showed better overall acceptability, when compared to Moringa Amla Millet Bar with 40% and 60% variations. There was a significant difference at 1% level among 20%, 40%, and 60% variations. The 20% level incorporation had a high product acceptability index of 88% compared to the 40% and 60% levels. The nutrient analysis of the accepted indicated that the following values per 100gm. 57.5mg of Iron,11.8 mg of vitamin C, 12.1g of Fiber, 12.2 mg of Protein, 345mg of calcium, 19.4mg of Zinc, and provides a substantial energy source of Kcal. Conclusion: The nutritious Moringa leaves with surplus health benefits shall be well utilized by incorporating it in various nutritious recipe preparation that may serve as iron supplements for growing adolescents.